The Reckoning: Financial Accountability and the Making and Breaking of Nations - Jacob Soll (Great Britain Penguin Books, 2015)
In The Reckoning, award-winning historian Jacob Soll shows how the use and misuse of financial bookkeeping has determined the fates of entire societies. Time and again, Soll reveals, good and honest accounting has been a tool to build successful companies, states and empires. Yet when it is neglected or falls into the wrong hands, accounting has contributed to cycles of destruction that continue to this day. Combining rigorous scholarship and fresh storytelling, The Reckoning traces the surprisingly powerful influence of accounting on financial and political stability, from the powerful Medici bank in the 14th century Italy to the 2008 financial crisis.
Keywords: Economics; History; Business; Finance; Accounting; Money; Politics; Nonfiction